Forecasting Presidential Nominations in 2016: #WePredictedClintonANDTrump. Issue 4 (12th October 2016) - Dowdle, Andrew J.; Adkins, Randall E.; Sebold, Karen; Cuellar, Jarred
ABSTRACT: A number of scholars successfully modeled and predicted presidential nomination outcomes from 1996–2008. However, dramatic changes occurred in subsequent years that would seem to make replicating these results challenging at best. Building on those earlier studies, we utilize a series of OLS models that included measures of preprimary resources and early campaign successes or failures to forecast that Hillary Clinton and Donald Trump would win the Democratic and Republican presidential nominations in 2016. This outcome suggests that some fundamental factors governing nomination outcomes have not changed despite the conventional wisdom.